Acoustic experience in the devotional scenology - Cirino, Giovanni (Revista Brasileira de Estudos da Presença, 2024)
This article discusses the acoustic universe of a scenic practice strongly anchored in devotion to São Benedito. Black tradition music and its relations with popular religiosities on the north coast of São Paulo are thought of as a context from which scenic practices are carried out. From sound, musical and morphological aspects we investigated the connections between symbolic elements of different religiosities present in representations of wars between mouros (Moors) and cristãos (Christians).